Through the Pentateuch chapter by chapter - Thomas, William Henry Griffith, 1861-1924; Gillespie, Winifred Griffith Thomas (Grand Rapids, MI Eerdmans, 1957)
Includes bibliographical references.
Keywords: Bible. O.T. Pentateuch -- commentaries